Identification and expression analysis of 19 CC chemokine genes in orange-spotted grouper (Epinephelus coioides). (August 2019) - Leu, Jiann-Horng; Tsai, Chi-Hang; Tsai, Jyh-Ming; Yang, Chia-Hsun; Hsueh, Chih-Yuan; Chou, Hsin-Yiu
Abstract: In this study, we describe 19 different CC chemokine genes from the orange-spotted grouper, Epinephelus coioides, identified by the analysis of the spleen transcriptome. Multiple sequence alignment of the 19 CC chemokines showed that although two genes, EcSCYA115 and EcSCYA117, shared 80% amino acid similarity (72% identity), the majority exhibited low similarity to each other. Phylogenetic analysis divided the 19 CC chemokines into six major groups. Tissue distribution analysis by RT-PCR showed that most of these chemokines were ubiquitously expressed in the 9 examined tissues, whereas some exhibited tissue-preferential expression patterns. For example, EcSCYA103 was preferentially expressed in fin and gill; EcSCYA109 in head kidney and spleen; EcSCYA114 in fin, gill, and liver; and EcSCYA119 in fin and stomach. Quantitative RT-PCR showed that after challenge with grouper iridovirus (GIV), four of the 19 CC chemokine genes, EcSYCA102, EcSYCA103, EcSYCA116, and EcSYCA118, were highly induced in the spleen. The expression of these four genes could also be upregulated by LPS and poly (I:C) challenges, suggesting that these four genes might be involved in immune response against invading pathogens. Highlights: 19 CC chemokine genes were identified from the spleen transcriptome of E. coioides . Two of them share 80% amino acid similarity, but the majority share low similarity. Phylogenetic analysis divided the 19 CC chemokines into six major groups. Most genes were ubiquitously expressed, but some had preferred expression patterns. 4 genes were highly induced in spleen by grouper iridovirus, LPS and poly (I:C).